O7.3. ALTERED HIPPOCAMPAL-STRIATAL-MIDBRAIN FUNCTION IN SUBJECTS AT CLINICAL HIGH RISK OF PSYCHOSIS. (9th April 2019) - Modinos, Gemma; Allen, Paul; Zugman, Andre; Dima, Danai; Azis, Matilda; Samson, Carly; Bonoldi, Ilaria; Quinn, Beverly; Gifford, George; Smart, Sophie; Antoniades, Mathilde; Bossong, Matthijs; et al.
Abstract: Background: The inappropriate attribution of salience to what would normally be irrelevant or neutral stimuli is a robust feature of psychotic disorders and is linked to altered subcortical dopaminergic signaling. Preclinical models suggest that the latter is driven by interactions within a hippocampal-striatum-midbrain circuit. Although novelty has been less investigated as a dimension of salience processing in psychosis than reward, preclinical evidence indicates that dopaminergic neurons in the midbrain code the salience of unexpected stimuli and respond to novel stimuli. Our first aim was to examine whether subjects at clinical high risk (CHR) for psychosis show altered activation and effective connectivity in the putative hippocampal-striatum-midbrain circuit using fMRI during the processing of novelty salience. The second aim was to examine the relationship between activation and effective connectivity within this circuit and the subsequent onset of a psychotic disorder, by following our CHR participants clinically for around 5 years after scanning to determine their clinical outcome. Methods: Seventy-six CHR participants and 31 healthy controls (HC) were studied using fMRI while performing a task that engaged novelty salience processing. The CHR sample was then followed clinically for a mean of 59.7 months (~5 years): during this period, 13 individuals (17%) developed a psychotic disorder (CHR-T) and 63 did not. Functional activation and effective connectivity within a hippocampal-striatal-midbrain circuit were compared between groups using the contrast Novel versus Neutral trials (indicating 'pure' novelty), using SPM12 and dynamic casual modelling (DCM12). Effects were considered significant at a voxel-wise threshold of p < 0.05 family-wise error corrected (FWE). Results: In CHR individuals, the hippocampal response to pure novelty was significantly attenuated compared to that in HC (p = 0.041 FWE). DCM12 revealed that pure stimulus novelty modulated effective connectivity from the hippocampus to the striatum, and from the midbrain to the hippocampus, significantly more in CHR participants than in HC. Conversely, pure stimulus novelty modulated connectivity from the midbrain to the striatum significantly less in CHR participants than in HC, and less in CHR participants who subsequently developed psychosis (CHR-T) than in CHR subjects who did not become psychotic. Discussion: These data indicate that both hippocampal activation and hippocampal-striatal-midbrain effective connectivity in the context of pure novelty salience are perturbed in people at CHR for psychosis, and that the later onset of psychosis is associated with alterations in midbrain-striatal connectivity. These findings are consistent with data from preclinical models of psychosis implicating alterations in a hippocampal–striatal-midbrain circuit in the development of psychosis.